HLA Diversity in Iraqi Population: Molecular Typing - Abbas, Ahmed A.H. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Different populations show various human leukocyte antigens (HLA). Data of HLA distribution is important in field of vaccines, therapy, Anthropology and for future studies of disease association with HLA.Objective: To highlight on frequency of HLA alleles in Iraqi population by using molecular technique.Patients and methods: Two hundred individuals were genotyped for HLA class I and II alleles by polymerase chain reaction sequence-specific oligonucleotides (PCR-SSO).Results: This study observed that the alleles with highest frequency were: [A*02(27.75%,A*01(10.75%,A*03(8%),B*51(17.75%),B*35(9%),B*07(6%),C*04(26.75%),C*07(20.25%),C6*0(9.75%),DRB1*02(17.5%,DRB1*07(17%),DRB1*04(14.75%)DQB1*01(25.5%),DQB1*03(21.75%),DQB1*02(19%)].Conclusion: Current study give additional information about HLA distribution in Iraqi Arab society and could be provide standard control for future studies about HLA association with disease in Iraq.